Flexible Transparent Electrodes Based on Silver Nanowires: Material Synthesis, Fabrication, Performance, and Applications. Issue 10 (20th August 2019) - Zhu, Yuwen; Deng, Yujun; Yi, Peiyun; Peng, Linfa; Lai, Xinmin; Lin, Zhongqin
Abstract: Owing to their compatibility with biology and large deformation, flexible electronics meet the demands for a wide range of applications that lie outside the capabilities of conventional rigid wafer‐based electronics. Devices such as solar cells, light‐emitting devices, touch screens, and wearable sensors have significantly advanced in recent years and changed human life. Flexible transparent electrodes are one of the most important components in flexible optoelectronic devices, collecting charges and transmitting light. Such electrodes based on silver nanowires (AgNWs), which exhibit superior mechanical flexibility, electrical and thermal conductivity, and optical transparency, are regarded as the most promising alternative to conventional indium tin oxide electrodes. However, some technical challenges, such as the uniformity and stability of AgNW networks, still exist and hinder the large‐scale commercialization of AgNW electrodes. Great efforts have been made in this field. A comprehensive survey of recent progress in flexible transparent AgNW electrodes in terms of performance criteria, material synthesis, fabrication process, performance enhancement, and future applications is provided. Finally, technical challenges and future trends are presented for the application of flexible transparent AgNW electrodes in flexible electronics. Abstract : Flexible transparent electrodes based on silver nanowires (AgNWs) are regarded as the most promising electrodes in flexible devices. Recent progress in flexible transparent AgNW electrodes is discussed in terms of performance criteria, material synthesis, fabrication process, performance enhancement, and future applications. Technical challenges and future trends are also presented.